2009
DOI: 10.1080/01674820902950553
|View full text |Cite
|
Sign up to set email alerts
|

Time since menarche, weight gain and body image awareness among adolescent girls: onset of eating disorders?

Abstract: Both time since menarche and increase in body weight following menarche are associated with increasing concerns about eating, body image and weight losing behaviour. Some young women develop eating disorders. Menarche and subsequent weight gain appear as a risk factor for the onset of eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Restraint affects satiation through restriction of FI as a means of controlling body weight (37). Self-regulation of FI is evident after menarche in 12-to 17-y-old girls, who limit their FI because of the concerns with body image (12). Although restraint associates with reduced FI in adult females (38) and restraint was higher in postpubertal girls, its role is unclear because no correlation was found between restraint and FI.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Restraint affects satiation through restriction of FI as a means of controlling body weight (37). Self-regulation of FI is evident after menarche in 12-to 17-y-old girls, who limit their FI because of the concerns with body image (12). Although restraint associates with reduced FI in adult females (38) and restraint was higher in postpubertal girls, its role is unclear because no correlation was found between restraint and FI.…”
Section: Discussionmentioning
confidence: 71%
“…Girls in this age range experience hormonal changes during puberty that may impact energy intake (11) and may use food and diet to address their negative perceptions of body image (12). Thus, our objective was to investigate the effect of TVV while eating and pubertal status on subjective appetite and mealtime FI 30 min after consumption of glucose (1.0 g/kg body weight) or noncaloric sweetened drink in 9-to 14-y-old girls.…”
mentioning
confidence: 99%
“…Paradoxically, normative pubertal changes which coincide with weight gain and increase in adiposity move many girls away from the ideal of a slender female figure prevalent in western culture; thus in many ways, normal puberty leads to a reduction in body image satisfaction among many girls (Abraham, Boyd, Lal, Luscombe, & Taylor, 2009;Levine & Smolak, 2006;Siegel, et al, 1999). Pubertal gains in adiposity are greater in early maturing females so it is not surprising that they more often report inferior body image satisfaction.…”
Section: Mediating Effectsmentioning
confidence: 99%
“…Several studies have suggested that the mean age of menarche has declined over the last few decades in developed (Fredriks et al, ; McDowell, Brody, & Hughes, ; Mendoza et al, ; Morris, Jones, Schoemaker, Ashworth, & Swerdlow, ; O'Connell, Gavin, Kelly, Molcho, & Nic Gabhainn, ) and developing (Jones, Griffiths, Norris, Pettifor, & Cameron, ; Loukid, Baali, & Hilali, ; Mao et al, ; Pathak, Tripathi, & Subramanian, ; Silva & Padez, ) countries. This has several public health implications because early onset of menarche has been linked to many disease conditions such as metabolic syndrome (Pathak et al, ), obesity (Bralić et al, ), type 2 diabetes(Dreyfus et al, ), ischemic heart disease and stroke (Jacobsen, Oda, Knutsen, & Fraser, ), depression (Stice, Presnell, & Bearman, ), eating disorders (Abraham, Boyd, Lal, Luscombe, & Taylor, ), breast cancer (Kotsopoulos et al, ), ovarian cancer (Jordan, Webb, & Green, ), endometrial cancer (Ali, ; Brinton et al, ), and overall mortality (Jacobsen, Heuch, & Kvale, ).…”
Section: Introductionmentioning
confidence: 99%